Assessing the mechanical behavior of glass and basalt reinforced vinyl ester composite under artificial seawater environment. (April 2022) - Osei Bonsu, Alex; Liang, Wenyan; Mensah, Comfort; Yang, Bin
Abstract: Glass and basalt fiber reinforced vinyl ester epoxy (GFRP and BFRP) composites offer considerable potential for underwater and deep sea applications. In spite of their increasing usage in various sectors, there are still questions concerning their long term reliability in marine environment. In this article, the response of GFRP and BFRP to seawater ageing and their subsequent mechanical properties were evaluated. The composites were fabricated by vacuum assisted resin injection technique and seawater aged at 30 0 C for 18, 28, 38, 258 and 305 days. By using scanning electron microscope (SEM), the failure of dry and seawater aged specimen after mechanical testing showed fiber breaking, debonding and sporadic fracturing along the laminate. This was due to higher moisture concentration in these areas during ageing. The results also revealed an overall steady decrease in tensile, flexural and impact strengths of seawater aged laminates with increasing ageing duration. Overall, the seawater ageing property of BFRP composites is almost identical to that of GFRP. The use of different nano-materials could also be explored in future works to address some drawbacks in the fiber–matrix interface durability after seawater ageing.